Belief Representations And Differentiated Instruction Among Mainstream Teachers In Inclusive Schools In Bisha City Saudi Arabia. - Alaklabi, Lamyaa Saad F (2024)
Inclusive education, which aims to cater to all students regardless of their backgrounds and abilities, faces challenges due to varying definitions and implementations globally. Teachers' beliefs towards inclusion and their beliefs in their roles and self-efficacy as well as practices of differentiated instruction are crucial factors in promoting inclusive practices, especially for students with learning difficulties. However, research on teachers' beliefs and practices of differentiated instruction in mainstream settings for students with learning difficulties is limited. This study aimed to examine teachers' beliefs and their implementation of differentiated instruction practices. The relationship between these factors as well as teachers’ demographic factors were also investigated. This study employed the mixed methods design that contains a cross-sectional survey using an online questionnaire in which a number of 162 Saudi school teachers were purposefully sampled. Second, semi-structured interviews with the eight teachers were conducted to support the questionnaire's findings. Inferential statistics, such as the T-test, ANOVA, Correlation, and Regression, were employed for the analysis of survey data, whereas thematic analysis was utilized for the analysis of semi-structured interviews data. The findings specifically emphasized the importance of teachers' beliefs about inclusive education, particularly their understanding of responsibilities as a crucial component. They also displayed strong beliefs in their protective role for students with learning disabilities and exhibited confidence in motivating students to collaborate.